2021
DOI: 10.1093/cid/ciab411
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Variant Under Investigation B.1.617.1 With Sera of BBV152 Vaccinees

Abstract: The drastic rise in the number of cases in Maharashtra, India has created a matter of concern for public health experts. Twelve isolates of VUI lineage B.1.617 were propagated in VeroCCL81 cells and characterized. Convalescent sera of the COVID-19 cases and recipients of BBV152 (Covaxin) were able to neutralize VUI B.1.617..

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(126 citation statements)
references
References 8 publications
2
124
0
Order By: Relevance
“…However, from the end of 2020, three divergent SARS-CoV-2 lineages evolved into fast-spreading variants that became known as variants of concern B.1.1.7 [United Kingdom (UK)] 23 , B.1.351 [South Africa (SA)] 24 and P.1 (Brazil) 25 . More recently, other lineages were added to this list: B.1.427, B.1.429 [California, United States of America (USA)], B.1.617 or B.1.617.1-3 [India] 23, 26, 27 , as well as several lineages of interest that carry the mutation E484K, including P.2 28 and B.1.1.7 containing E484K. These variants present alterations in the spike protein that change its properties: increase transmissibility and virulence 29, 30 and/or escape immunity developed by natural infection 31, 32 , therapies 3335 , vaccination 36 , detection 37 ; and change the host species range 38 .…”
Section: Main Textmentioning
confidence: 99%
“…However, from the end of 2020, three divergent SARS-CoV-2 lineages evolved into fast-spreading variants that became known as variants of concern B.1.1.7 [United Kingdom (UK)] 23 , B.1.351 [South Africa (SA)] 24 and P.1 (Brazil) 25 . More recently, other lineages were added to this list: B.1.427, B.1.429 [California, United States of America (USA)], B.1.617 or B.1.617.1-3 [India] 23, 26, 27 , as well as several lineages of interest that carry the mutation E484K, including P.2 28 and B.1.1.7 containing E484K. These variants present alterations in the spike protein that change its properties: increase transmissibility and virulence 29, 30 and/or escape immunity developed by natural infection 31, 32 , therapies 3335 , vaccination 36 , detection 37 ; and change the host species range 38 .…”
Section: Main Textmentioning
confidence: 99%
“…We also identified seven patients infected with B.1.617family variants, genotypes now causing extensive disease in India. [43][44][45] A key finding from our study was the very rapid trajectory of VOC B.1.1.7 in metropolitan Houston, an area with a population size of approximately 7 million. Several investigators have reported previously that patients infected with the B.1.1.7 VOC have significantly lower Ct values on initial diagnosis, but this has not been a universal finding.…”
Section: Discussionmentioning
confidence: 65%
“…We also identified seven patients with COVID-19 caused by B.1.617.1 or B.1.617.2, variants reported to be causing widespread disease and extensive public health concern in India. [43][44][45][46][47][48] In the aggregate, our genome data show that VOC and VOI now account for the great majority of all new COVID-19 cases in our region.…”
Section: [Introduction]mentioning
confidence: 64%
“…However, B.1.1.7 and P.1 have immune evasion capability 38,39 for carrying neutralization-resistant mutants, such as 501Y and 484K. A recently evolved Indian lineage B.1.617 also carried a point mutation in 28881, but the mutation is G28881T not G28881A 40 . Meanwhile, there is no mutation in 28882 and 28883.…”
Section: Discussionmentioning
confidence: 99%